KOMPARASI PENGGUNAAN TEPUNG JAGUNG DARI VARIETAS BERBEDA TERHADAP KUALITAS KREMUS - Setiawati, Bernadetta Budi (Jurnal Ilmu-Ilmu Pertanian, 2017)
Corn is second search of food after rice which is found higher protein content and available with affordable price. The aims of this research are to determine differences in quality sensory kremus cookies with the use of varieties of Bisi-2 and Srikandi Putih in terms of colour, flavour, taste and texture indicator; and the preference level panellists to kremus cookies. Research method with comparative study of the use of corn flour varieties Bisi 2 and Srikandi Putih. Data analysis with t-test to know difference of kremus cookies quality of corn flour and descriptive percentage is used for preference test that is know the level of preference to product kremus corn flour. The results of research on the use of corn flour varieties Srikandi Putih and Bisi-2 there is a real difference in the flavour indicator. Sample of the best corn flour kremus cookies of corn flour bisi 2 varieties showed the highest mean value of 3,51 with colour indicator 4,08; flavour 2,97; taste 3,61 and texture 3,39. In the preference test, the panellist liked of kremus cookies of varieties of Bisi-2 corn flour with the colour indicator showing an average value of 4,11 (82,22%) likes criteria, flavour average value 3,56 (71,11%) likes criteria, taste average value of 3,94 (78,89%) likes criteria, texture average value 3,78 (76%) likes criteria.